Moving With Pain: What Principles From Somatic Practices Can Offer to People Living With Chronic Pain - Meehan, Emma; Carter, Bernie (Frontiers in Psychology, 2021)
This article brings together research from the fields of chronic pain management and somatic practices to develop a novel framework of principles to support people living with persistent pain. These include movement-based approaches to awareness of the internal body (interoception), the external environment (exteroception) and movement in space (proprioception). These significantly work with the lived subjective experiences of people living with pain, to become aware of body signals and self-management of symptoms, explore fear and pleasure of movement, and understand how social environments impact on pain. This analysis has potential to create new ways of supporting, understanding and articulating pain experiences, as well as shaping the future of somatic practices for persistent pain.